2015
DOI: 10.1126/science.1257026
|View full text |Cite
|
Sign up to set email alerts
|

Experimental observation of a generalized Gibbs ensemble

Abstract: The description of the non-equilibrium dynamics of isolated quantum many-body systems within the framework of statistical mechanics is a fundamental open question. Conventional thermodynamical ensembles fail to describe the large class of systems that exhibit nontrivial conserved quantities, and generalized ensembles have been predicted to maximize entropy in these systems. We show experimentally that a degenerate one-dimensional Bose gas relaxes to a state that can be described by such a generalized ensemble.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
581
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 538 publications
(600 citation statements)
references
References 46 publications
(13 reference statements)
15
581
0
1
Order By: Relevance
“…The connected correlation function G (N ) con (z, z ) for N > 2 is therefore a direct measure of their interactions. In contrast, the more commonly used correlation functions e i[ϕ(z)−ϕ(z )] and their higher-order generalisations [20] contain G (N ) con (z, z ) up to arbitrary order even for the 2 nd -order function and are therefore not suitable for studying these interaction properties (see Methods and the SI).…”
Section: Arxiv:150503126v2 [Cond-matquant-gas] 19 May 2017mentioning
confidence: 99%
See 1 more Smart Citation
“…The connected correlation function G (N ) con (z, z ) for N > 2 is therefore a direct measure of their interactions. In contrast, the more commonly used correlation functions e i[ϕ(z)−ϕ(z )] and their higher-order generalisations [20] contain G (N ) con (z, z ) up to arbitrary order even for the 2 nd -order function and are therefore not suitable for studying these interaction properties (see Methods and the SI).…”
Section: Arxiv:150503126v2 [Cond-matquant-gas] 19 May 2017mentioning
confidence: 99%
“…With the rapid progress in quantum gas experiments [16], measuring higher-order correlation functions [17][18][19][20] is now within reach. To illustrate the power of the above concepts to analyse a non trivial interacting quantum many-body system, we experimentally investigate two tunnel-coupled one-dimensional (1D) bosonic superfluids, realised with quantum degenerate 87 Rb atoms trapped in a double-well (DW) potential with a freely relative DOF DW potential adjustable tunnel-coupling FIG.…”
mentioning
confidence: 99%
“…In particular, in Refs. [16][17][18]24] prethermal states in the relative phase of a suddenly split condensate have been identified that have been stable on the experimentally accessible time scales. For the latter experiments, the cubic nonlinearity studied in the present work constitutes the leading order correction to the quadratic theory in a gradient expansion.…”
Section: Interacting Luttinger Liquidmentioning
confidence: 99%
“…Concerning the relevance of the interacting Luttinger model, before closing the section, we would like to mention that only recently pioneering experiments in ultra-cold gases both in and out of equilibrium explored the transient and prethermalization dynamics of systems [16][17][18][19][20][21][22][23][24][25][26][68][69][70] effectively described by a quadratic Luttinger model, the bosonic theory of the Hamiltonian in Eq. (2.2).…”
Section: Interacting Luttinger Liquidmentioning
confidence: 99%
See 1 more Smart Citation